THE “COMFORT ZONE” OF GENDER INEQUALITY: A REFLECTION - OsonduOti, Adaora (The Gender Truth Journal, 2024)
Globally, gender inequality has remained a persistent problem confronting humanity. The global community recognizes it as “an unfinished business of our time”. Despite centuries of efforts, the World Economic Forum Global Gender Gaps reported in June 2024 that achieving gender equality in all regions may not be possible until the year 2158. While diverse factors are known to contribute to gender inequality, this paper argues that gender inequality persists because gender inequality is a “comfort zone”. Making use of documentary sources including relevant examples of how “this” comfort zone plays out in gender relations and interactions between men and women, especially in Africa, the author tries to establish the theory of the comfort zone of gender inequality. Findings revealed that gender inequality is beneficial to the powers-that-be, and being in a comfort zone of gender inequality is a choice. In other words, the choice to keep gender inequality alive is a rational one and it is authoritative power that sustains it. Given “the comfort” that goes with gender inequality, it then follows that commitment to gender equality is often low, making the efforts to achieve gender equality a struggle all over the world. It is therefore recommended that feminists and human activists keep up with the struggle because, just like sit-tight presidents who find it difficult to transfer power or leave office, those in the comfort zone of gender inequality would not want to leave the zone, as it is a “familiar” terrain. Thus, a need for more “push” and a consistent struggle to achieve gender equality.